High Risk Pregnancy and Infant Outcome in the Kassena-Nankana District - An Analysis of the Panel Survey of the Navrongo Health Research Centre - Kwarteng, A.N. (University of Ghana, 1997)
High Risk Pregnancy is defined as a pregnancy that may have a predisposition to an unfavourable outcome, either for the mother or the child, as a result of certain factors that may increase the potential of poor outcome. Many of these risk factors have been widely studied, are well documented and as such have gained wide acceptance. The detection of risk in pregnancy is included in many national policies and maternal and child health services, particularly antenatal care. The Kassena-Nankana District of the Upper East Region, from where this data was collected, is one such area that is largely traditional and pronatalist, with high fertility and high mortality rates, much the same as most rural areas throughout the country. As such, it would thus seem that a large majority of women would be at increased risk for an unfavourable outcome. It was thus the intention of this analysis, to identify pregnant women who fall into this high risk category within the district and to examine whether their risk status has an effect on their infant outcome. For the purpose of the study, four risk factors and combinations of them were investigated. The factors which placed a woman at risk were age (below 18 years of age or more than 34 years of age), parity (no previous births or has given birth 3 times or more), short birth interval (current pregnancy has occurred within 2 years of a previous birth) and past poor obstetric history (a history of previous neonatal or infant deaths). Other socio-demographic factors such as educational status, use of antenatal care, place and assistance at delivery were also examined as to their importance to infant survival. The prevalence of high risk pregnancy was found to be high, with over 80 percent of the women having at least one risk factor. It was surprising to find very few perinatal and neonatal deaths. Infant deaths were more, but this required cautious interpretation since not all the infants would have reached the age of one year. Because of the small number of deaths, only two risk factors or combination of risk factors were found to be statistically significant. These were short birth interval as a single risk factor and short birth interval in combination with past obstetric history. A factor that showed a surprising association was use of antenatal care. Women who received antenatal care from qualified health personnel such as a doctor or a nurse, had a higher risk of poor outcome. Evidently, that improvements in the environmental conditions as well as better utilization of maternity services, especially family planning, could have a substantial effect in improving the infant survival in a rural area such as Kassena-Nankana.